Poverty Reduction and Growth Trust : 2016-17 Borrowing Agreements with the Government of Canada, De Nederlandsche Bank NV, and the Bank of Korea. (Policy Papers; Policy Paper ;, 2017)
The IMF, as Trustee of the Poverty Reduction and Growth Trust (PRGT or Trust), has entered into a new borrowing agreement with the Government of Canada (Canada), and has entered into amendments to the 2010 borrowing agreement with De Nederlandsche Bank NV (The Netherlands) and the 2011 borrowing agreement with the Bank of Korea (Korea). The new borrowing agreement with Canada and the amendments to the borrowing agreements with The Netherlands and Korea will each provide new resources of SDR 500 million to the General Loan Account of the PRGT, for a total amount of SDR 1.5 billion in new PRGT lending resources. Except for the increase in amount for drawings, all other elements of the borrowing agreements with The Netherlands and Korea remain unchanged.